Major Ion Chemistry Data of WAIS Divide Ice Core Brittle Ice - Cole-Dai, Jihong (IEDA: US Antarctic Program Data Center, 2014)
Abstract: The brittle ice section (577-1300 m) of the main WAIS Divide ice core (WDC06A) was analyzed for major ion concentrations with ion chromatography.